Unveiling post-vaccination proteomic signatures in SARS-CoV-2 infection-naïve individuals associated with Omicron breakthrough infections - Yiwen Liu; Eric Lu; Katherine D. Ellingson; James Hollister; Tuo Liu; Wadana Hamzazai; Shawn C. Beitel; Alberto J. Caban-Martinez; Manjusha Gaglani; Allison L. Naleway; Lauren E. W. Olsho; Andrew L. Phillips; et al. (PLoS ONE, 2026)
Background Given the persistence of the SARS-CoV-2 virus, it is important to understand the proteome associated with breakthrough infections among COVID-19 vaccinated individuals. Methods We conducted a nested case-control study within the frontline worker HEROES-RECOVER cohorts to specify a study population of SARS-CoV-2 infection-naïve participants who had a third dose of COVID-19 origin strain WA-1 monovalent mRNA vaccine from August 2021 to January 2022. We compared serum proteomic profiles for those who subsequently experienced Omicron breakthrough infections with those of matched controls without infections. Our study leveraged proteomics data generated from the SomaScan Platform and adopted a robust feature selection method, elastic net regularized conditional logistic regression with bootstrapping, to identify key proteins. Enrichment analyses were performed to investigate biological pathways. Results We identified 28 significant proteins out of over 7,000 candidate proteins. Key findings included downregulated chemokines (CXCL2, CXCL3, CCL19, CCL23) and elevated cytokine IL-7 levels in breakthrough cases, with pathway analysis revealing enrichment in chemokine signaling and cytokine-cytokine interaction pathways. Other key proteins, such as LGALS1, HAVCR2, and SELE were upregulated in breakthrough cases. Discussion These results reveal potential immune response mechanisms in breakthrough infections, characterized by viral immune evasion and compensatory T-cell regeneration. The identified biomarkers may provide valuable insights for future predictive profiles and therapeutic strategies.